Phylogeny and genomic analysis of Shewanella cutis sp. nov., isolated from freshwater pufferfish - Das, Lipika; Kujur, Ritu Rani Archana; Debnath, Tanmoy; Das, Subrata K (Folia microbiologica, 2024)
Three closely related, aerobic, Gram-stain-negative, motile, rod-shaped bacterial strains (PS-2T, PS-17, and PS-19) were isolated from the skin of freshwater pufferfish (Tetraodon cutcutia). Colonies are pinkish-colored. The optimum growth occurred at 28-30 °C, and the pH was 6.5-7. The major cellular fatty acids were C16:1 ω7c, iso-C15.0, C17:1 ω8c, C18:1 ω7c, and C16:0. The predominant polar lipids were phosphatidylglycerol, phosphatidylethanolamine, and amino lipids. The genome size of strain PS-2T is 4.8 Mbp, and the G + C content was 46.0%. The major fraction of genes were associated with biological processes (45.64%), followed by molecular function (29.86%) and cellular components (24.49%). The unique genes identified in strain PS-2T secreted cyanophycinase, UDP-N-acetylglucosamine 2-epimerase, methyltransferase, kynureninase, ADA regulatory protein, biphenyl degradation, thermostable carboxypeptidase 1, tetrathionate respiration, etc. In addition, alanine and glutamate racemases were present. The 16S rRNA gene sequences shared 98.83-99.24% similarity with the closely related type strains of Shewanella. The ANI and AAI of strain PS-2T with reference type strains of the genus Shewanella were below 95-96%, and the corresponding dDDH values were below 70%. A phylogenetic tree based on 16S rRNA gene sequences and genome-wide core genes revealed that strain PS-2T clustered with Shewanella oneidensis LMG 19005T in both phylogenetic trees. Based on the polyphasic analysis, the new isolates (PS-2T, PS-17, and PS-19) represent a novel species of Shewanella, for which Shewanella cutis sp. nov. is proposed. The type strain is PS-2T (= TBRC 15838T = NBRC 115342T).
Keywords: zastoupení bazí; Tetraodontiformes; Shewanella; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; mastné kyseliny; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Genome, Bacterial; sladká voda; kůže; Fatty Acids; Fresh Water; Genomics; genom bakteriální; DNA, Bacterial; DNA bakterií; Animals; Phospholipids; Skin; zvířata; Base Composition; fosfolipidy; RNA ribozomální 16S; Bacterial Typing Techniques; genomika